Psychological analysis of religiosity in the perspective of interpersonal communication - Jaworski, Romuald (Studia Psychologica: Theoria et praxis, 2002)
In the psychology of religion it has been possible to trace the development of approaches to the phenomenon of religiosity. The main thesis of this article concerns the heuristic value of the theory of interpersonal communication for investigations about religiosity. The greater chance of enriching the knowledge of psychology of religion is an analysis of religiosity in context, and in this perspective, also of knowledge of the subject of interpersonal communication. The subject of considerations and searches is the psychology of religion and pastoral psychology. For analysis of religious phenomenon there is a particularly interesting and inspiring return of attention to the personal dimension of men's contact with God, which have place in religious experiences. Treating religiosity as interpersonal relationship opens new possibilities of investigation of religious phenomena. It could be helpful for achievement of improved interpersonal communication. Change of paradigm permits growing of psychology of religi and settling it in perspective of communication and interpersonal relationship, and also to see many religious experiences in a new light. This perspective permits deepening understanding of the dynamics and aim of religious development. It makes possible deepened analysis of conflicts and religious crises as well. It opens new areas of investigation, not only to put new questions, but also stimulating elaboration of new strategy and investigative methods.